Feasible Design of a Free Electron Laser Based on the Smith–Parsell Effect - Aleinik A. N. Aleksandr Nikonorovich; Aryshev A. S.; Kalinin B. N.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Saruev G. A. Gennady Alekseevich; Chefonov O. V. (2004, 2004)
Title screen